Primary versus Delayed Primary Closure of Laparotomy Wounds in Children Following Typhoid Ileal Perforation in Ile-Ife, Nigeria - Inyang, Akan W. (Afr J Paediatr Surg, 2017)
BACKGROUND: The optimal management strategy for dirty abdominal wounds has yet to be determined, but studies indicate that delayed primary closure (DPC) may be a reliable method of reducing surgical site infection (SSI) rate in these wounds. In this study, of dirty laparotomy wounds following typhoid ileal perforation (TIP), the SSI rate, incidence of wound dehiscence, and length of hospital stay (LOS) are compared in wounds primarily closed to those closed in the delayed primary fashion. PATIENTS AND METHODS: The study was conducted over a 12-month period. Consecutive patients aged between 0 and 15 years with typhoid ileal perforation (TIP) were enrolled and prospectively randomized to test (DPC) group and control (PC) group. Data including age, sex, diagnosis, type of wound closure, SSI, wound dehiscence, time to wound healing, and LOS were obtained and analyzed using SPSS version 16. RESULTS: Fifteen patients were recruited into DPC group while 19 patients were allocated to the PC group. The SSI rate was 80% in the DPC group compared to 63.2% in the PC group (P = 0.451). 17.6% of patients in the DPC group and 8.8% in the PC group had wound dehiscence, respectively (P = 0.139). The difference in LOS although longer in the DPC group was not statistically significant (DPC 23.47 ± 9.2, PC 17.68 ± 18.9, P = 0.123). CONCLUSION: DPC did not reduce the incidence of SSI and wound dehiscence, nor shorten LOS compared to PC. Therefore, PC of dirty wounds appears safe for the pediatric population and should be advocated.